THE EFFECT OF SHOPEE E-COMMERCE TRUST ON CUSTOMER LOYALTY THROUGH THE INTERVENING VARIABLE OF PURCHASING DECISIONS (STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MAKASSAR STATE UNIVERSITY) - Fathurrahman Fathurrahman; Uhud Darmawan Natsir; Muhammad Ilham Wardhana Haeruddin; Siti Hasbiah; Ilma Wulansari Hasdiansa (Adiba Aisha Amira, 2025)
The purpose of this study was to determine the effect of Shopee's E-Commerce Trust on Customer Loyalty in active students of the Faculty of Economics and Business, Universitas Negeri Makassar through Purchasing Decisions as an Intervening Variable. The sample used was 100 Shopee consumer respondents who had been selected based on predetermined criteria. The data collection technique was carried out by questionnaire and literature study. The data analysis technique consists of an Outer Model (Measurement Model) consisting of Convergent Validity, Discriminant Validity, Multicollinearity, and Composite Reliability, then the Structural Model (Inner Model) with the R-Square test, Patch Coefficients, Total Indirect Effect, and Goodness of Fit test. Based on the results of the study, it shows that the E-commerce Trust variable has a positive and significant effect on Customer Loyalty, the Purchasing Decision variable has a positive and significant effect on Customer Loyalty, the E-commerce Trust variable has a positive and significant effect on Purchasing Decisions, and the E-commerce Trust variable has a positive and significant effect on Customer Loyalty through Purchasing Decisions.